A Systematic Review on the Affordability of a Healthful Diet for Families in the United States. Issue 1 (18th August 2014) - Horning, Melissa L.; Fulkerson, Jayne A.
Abstract Objectives As obesity rates remain alarmingly high, the importance of healthful diets is emphasized; however, affordability of such diets is disputed. Market basket surveys (MBSs) investigate the affordability of diets for families that meet minimum daily dietary requirements using actual food prices from grocery stores. This review paper describes the methods of MBSs, summarizes methodology, price and affordability findings, limitations, and suggests related policy and practice implications. Design and Sample This is a systematic review of 16 MBSs performed in the United States from 1985 to 2012. A comprehensive multidisciplinary database search strategy was used to identify articles meeting inclusion criteria. Results Results indicated MBS methodology varied across studies and price data indicated healthful diets for families are likely unaffordable when purchased from small‐ to medium‐sized stores and may be unaffordable in larger stores when compared to the Thrifty Food Plan. Conclusions Using a social ecological approach, public health nurses and all public health professionals are prime advocates for increased affordability of healthful foods. This study includes policy advocacy, particularly in support of Supplemental Nutrition Assistance Program benefits for low‐income families. Future research implications are provided, including methodological recommendations for consistency and quality of forthcoming MBS research.